Detection of atrial fibrillation in primary care with radial pulse palpation, electronic blood pressure measurement and handheld single-lead electrocardiography: a diagnostic accuracy study - Wim A M Lucassen; Henk C P M van Weert; Bjorn Winkens; Henri E J H Stoffers; J André Knottnerus; Steven B Uittenbogaart; Nicole Verbiest-van Gurp; Petra M G Erkens (BMJ Open)
Objective To determine the diagnostic accuracy of three tests—radial pulse palpation, an electronic blood pressure monitor and a handheld single-lead ECG device—for opportunistic screening for unknown atrial fibrillation (AF).Design We performed a diagnostic accuracy study in the intention-to-screen arm of a cluster randomised controlled trial aimed at opportunistic screening for AF in general practice. We performed radial pulse palpation, followed by electronic blood pressure measurement (WatchBP Home A) and handheld ECG (MyDiagnostick) in random order. If one or more index tests were positive, we performed a 12-lead ECG at shortest notice. Similarly, to limit verification bias, a random sample of patients with three negative index tests received this reference test. Additionally, we analysed the dataset using multiple imputation. We present pooled diagnostic parameters.Setting 47 general practices participated between September 2015 and August 2018.Participants In the electronic medical record system of the participating general practices (n=47), we randomly marked 200 patients of ≥65 years without AF. When they visited the practice for any reason, we invited them to participate. Exclusion criteria were terminal illness, inability to give informed consent or visit the practice or having a pacemaker or an implantable cardioverter-defibrillator.Outcomes Diagnostic accuracy of individual tests and test combinations to detect unknown AF.Results We included 4339 patients; 0.8% showed new AF. Sensitivity and specificity were 62.8% (range 43.1%–69.7%) and 91.8% (91.7%–91.8%) for radial pulse palpation, 70.0% (49.0%–80.6%) and 96.5% (96.3%–96.7%) for electronic blood pressure measurement and 90.1% (60.8%–100%) and 97.9% (97.8%–97.9%) for handheld ECG, respectively. Positive predictive values were 5.8% (5.3%–6.1%), 13.8% (12.2%–14.8%) and 25.2% (24.2%–25.8%), respectively. All negative predictive values were ≥99.7%.Conclusion In detecting AF, electronic blood pressure measurement (WatchBP Home A), but especially handheld ECG (MyDiagnostick) showed better diagnostic accuracy than radial pulse palpation.Trial registration number Netherlands Trial Register No. NL4776 (old NTR4914).